Identification, prevalence and pathogenicity of Colletotrichum species causing anthracnose of Capsicum annuum in Asia - Dilani D. de Silva; Johannes Z. Groenewald; Pedro W. Crous; Peter K. Ades; Andi Nasruddin; Orarat Mongkolporn; Paul W. J. Taylor (IMA Fungus)
Abstract Anthracnose of chili (Capsicum spp.) causes major production losses throughout Asia where chili plants are grown. A total of 260 Colletotrichum isolates, associated with necrotic lesions of chili leaves and fruit were collected from chili producing areas of Indonesia, Malaysia, Sri Lanka, Thailand and Taiwan. Colletotrichum truncatum was the most commonly isolated species from infected chili fruit and was readily identified by its falcate spores and abundant setae in the necrotic lesions. The other isolates consisted of straight conidia (cylindrical and fusiform) which were difficult to differentiate to species based on morphological characters. Taxonomic analysis of these straight conidia isolates based on multi-gene phylogenetic analyses (ITS, gapdh, chs-1, act, tub2, his3, ApMat, gs) revealed a further seven known Colletotrichum species, C. endophyticum, C. fructicola, C. karsti, C. plurivorum, C. scovillei, C. siamense and C. tropicale. In addition, three novel species are also described as C. javanense, C. makassarense and C. tainanense, associated with anthracnose of chili fruit in West Java (Indonesia); Makassar, South Sulawesi (Indonesia); and Tainan (Taiwan), respectively. Colletotrichum siamense is reported for the first time causing anthracnose of Capsicum annuum in Indonesia and Sri Lanka. This is also the first report of C. fructicola causing anthracnose of chili in Taiwan and Thailand and C. plurivorum in Malaysia and Thailand. Of the species with straight conidia, C. scovillei (acutatum complex), was the most prevalent throughout the surveyed countries, except for Sri Lanka from where this species was not isolated. Colletotrichum siamense (gloeosporioides complex) was also common in Indonesia, Sri Lanka and Thailand. Pathogenicity tests on chili fruit showed that C. javanense and C. scovillei were highly aggressive, especially when inoculated on non-wounded fruit, compared to all other species. The existence of new, highly aggressive exotic species, such as C. javanense, poses a biosecurity risk to production in countries which do not have adequate quarantine regulations to restrict the entry of exotic pathogens.